Overexpression of α (1,6) fucosyltransferase associated with aggressive prostate cancer - Wang, Xiangchun (Oxford University Press, 2014)
Aberrant protein glycosylation is known to be associated with the development of cancers. The aberrant glycans are produced by the combined actions of changed glycosylation enzymes, substrates and transporters in glycosylation synthesis pathways in cancer cells. To identify glycosylation enzymes associated with aggressive prostate cancer (PCa), we analyzed the difference in the expression of glycosyltransferase genes between aggressive and non-aggressive PCa. Three candidate genes encoding glycosyltransferases that were elevated in aggressive PCa were subsequently selected. The expression of the three candidates was then further evaluated in androgen-dependent (LNCaP) and androgen-independent (PC3) PCa cell lines. We found that the protein expression of one of the glycosyltransferases, α (1,6) fucosyltransferase (FUT8), was only detected in PC3 cells, but not in LNCaP cells. We further showed that FUT8 protein expression was elevated in metastatic PCa tissues compared to normal prostate tissues. In addition, using tissue microarrays, we found that FUT8 overexpression was statistically associated with PCa with a high Gleason score. Using PC3 and LNCaP cells as models, we found that FUT8 overexpression in LNCaP cells increased PCa cell migration, while loss of FUT8 in PC3 cells decreased cell motility. Our results suggest that FUT8 may be associated with aggressive PCa and thus is potentially useful for its prognosis.